SCLEROSING LYMPHANGITIS OF THE PENIS – A CASE REPORT - Bjekić, Milan (HEALTH CARE, 2025)
Background/Aim: Sclerosing lymphangitis of the penis is a rare non-infectious condition that most commonly occurs in young sexually active individuals. It is characterized by the sudden appearance of a painless, band-like thickening in the area of the coronal sulcus, which is preceded by intense sexual intercourse or masturbation. The aim of this paper was to present a patient with the characteristic clinical picture of non-venereal sclerosing lymphangitis of the penis and to remind healthcare professionals, particularly dermatologists and urologists, of this rare condition. Case report: A 32-year-old male in good general health presented to a dermatologist with a painless thickening on the shaft of the penis that appeared after intense sexual intercourse. Clinical examination revealed the presence of a painless, translucent, thick, band-like structure with a cartilaginous consistency behind the corona of the glans, without enlargement of regional lymph nodes. Serological tests for syphilis did not indicate recent infection. The patient was advised to refrain from sexual activity, and after four weeks, the changes had resolved. Conclusion: Sclerosing lymphangitis of the penis is a rare benign, non-infectious condition that occurs in younger sexually active individuals and often causes concern. It can present a diagnostic challenge for healthcare providers due to its clinical similarity to superficial penile vein thrombophlebitis or atypical early syphilitic penile lesions. Therefore, it is important that urologists and dermatologists do not overlook it in their daily practice.